A giant cholesteatoma of the mastoid extending into the foramen magnum: A case report and review of literature - Seidu A Richard; Li Qiang; Zhi Gang Lan; Yuekang Zhang; Chao You (MDPI AG, 2018)
Cholesteatomas are very rare benign, progressive lesions that have embryologic derivation and usually result in progressive exfoliation and confinement of squamous epithelium behind an intact or preciously infected tympanic membrane. To the best of our understanding no reports demonstrates the extension of cholesteatoma from the temporal bone into the foramen magnum. We therefore present a case of cholesteatoma extending down into the foramen magnum. We report a case of 67- year-old man with a giant cholesteatoma extending into the foramen magnum without substantial destruction of the mastoid and petrous temporal bones. The patient's major symptoms were recurrent tinnitus in the left ear and dizziness with unilateral conductive hearing loss. A working diagnosis of cholesteatomas was made combining the symptoms and magnetic resonance imaging findings. He was then successfully operated on with very minimal postoperative complications. Cholesteatomas originating from the mastoid bone often linger with the patients for many years in a subclinical state and progress into a massive size before causing symptoms. Patients with unilateral conductive hearing loss who are otherwise asymptomatic and have a normal tympanic membrane should be suspected with a progressive cholesteatoma. Cholesteatoma should be one of the working diagnosis when an elderly patient present with unilateral conductive hearing loss that is associated with tinnitus and dizziness.